Covalent immobilization of phosphotungstic acid and amino acid on metal-organic frameworks with different structures: Acid-base bifunctional heterogeneous catalyst for the production of biodiesel from insect lipid. (July 2023) - Feng, Weiliang; Tie, Xinlong; Duan, Xiaoling; Yan, Su; Fang, Si; Sun, Peiyong; Gan, Lin; Wang, Tielin
Abstract: To provide more acid-base active sites for the conversion of the insect lipid into biodiesel, three bifunctional heterogeneous catalysts (amino acid-PTA/ZIF-8) with different structures were designed and compared by modifying ZIF-8 with amino acid and phosphotungstic acid (PTA) as active species in the current research. The as-prepared amino acid-PTA/ZIF-8 composite catalyst features a large surface area and an increased acidity and basicity, thus combining the merits of acid and base with the heterogeneous microenvironment of ZIF-8. Meanwhile, various methods were used to investigate the physicochemical properties of the synthesized composite catalyst. Furthermore, the effects of reaction conditions on the esterification and transesterification of the acid model lipids were used to assess the best catalytic activity process. The optimum conditions (molar ratio of Arginine/PTA = 2:1, weight ratio of Arg2 PTA/ZIF-8 = 3:1, reaction temperature = 60 °C, catalyst loading = 3 wt%, methanol/lipid molar ratio = 9:1, and stirring rate = 500 rpm) resulted in a maximum lipid conversion to biodiesel of 94.15%. In addition, the stability and reusability of the prepared catalysts with different structures during four reaction cycles were also demonstrated. Finally, the physicochemical properties of the biodiesel studied were measured and compared to the ASTM standard. Hence, this work provides great potential for acid-base functionalization of porous materials for future biodiesel production.